Characteristics of Homestays in Banyuwangi Regency Tourism Villages - Jannah, Reni Nur; Wijaya, Jemi Cahya Adi; Purwaningtyas, Ayu; Nurhalimah, Nurhalimah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The existence of homestays in tourist villages is expected to reflect the characteristics and cultural characteristics of the village with the aim of providing a different experience for guests or tourists. The purpose of this study is to explore the characteristics of homestays spread across tourist villages in Banyuwangi Regency through observation and interviews with a three-step analysis technique, namely, data condensation, presenting data and drawing conclusions or verification. The results of this study indicate that there are different characteristics between homestays in tourist villages with advanced and developing status based on the Banyuwangi Regent's Decree in 2021. Differences in characteristics are based on the criteria of the ASEAN Homestay Standard 2016.